Diversifikasi Pasar dan Daya Saing Ekspor Produk Olahan Kopi Indonesia ke Negara Emerging Market Terpilih - Mukhlisul Amal Mustofa; Achmad Syahrul Choir (Politeknik Statistika STIS, 2021)
Coffee exports in Indonesia are still dominated by coffee beans, but the export value has decreased. In contrast, exports of Indonesian Coffee Products (POKI) tend to increase during 2015-2019. However, POKI's exports are still dominated by one country, namely the Philippines, so its exports are greatly affected by the condition of that country. This causes POKI exports to be vulnerable to instability. Therefore, it is necessary to diversify the market for POKI exports. This study analyzes the level of diversification of POKI's export market and its export competitiveness to several emerging market countries for diversification purposes during 2010-2019. The measures used are Hirschman Index, Revealed Comparative Advantage, Export Product Dynamic, and X-Model. As a result, POKI's export market diversification in aggregate has not been good enough.The competitiveness of POKI's exports to several emerging market destination countries is quite good with a strategic position. The results of the X-model, obtained five countries that can optimistically become the destination of diversification.